Shaded Apertures and Bartlet Apertures for Two Line Resolutions on Aperture Shaping - Kumar, T. Kiran; Narsaiah, A.; Kumar, K. Vinod; Sagar, D. Karuna (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
Several criteria of resolution, e.g. Rayleigh Criterion, Sparrow Criterion etc. are used for assessment of two line resolution of unobscured imaging systems. The choice of particular criterion is usually dictated by the threshold contrast sensitivity of the detector used for the purpose. Annular apertures and Shrink apertures have a narrower central lobe in the Line spread function and therefore they are expected to provide improved two line resolution characteristics compared to their unobscured counterparts. The interrelationship between the dip in central intensity, degree of central obscuration and the least resolvable distance are studied in this paper.